2004
DOI: 10.1016/j.neuroimage.2003.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Mapping distributed sources of cortical rhythms in mild Alzheimer's disease. A multicentric EEG study

Abstract: The study aimed at mapping (i) the distributed electroencephalographic (EEG) sources specific for mild Alzheimer's disease (AD) compared to vascular dementia (VaD) or normal elderly people (Nold) and (ii) the distributed EEG sources sensitive to the mild AD at different stages of severity. Resting EEG (10-20 electrode montage) was recorded from 48 mild AD, 20 VaD, and 38 Nold subjects. Both AD and VaD patients had 24-17 of mini mental state examination (MMSE). EEG rhythms were delta (2-4 Hz), theta (4-8 Hz), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
272
1
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(330 citation statements)
references
References 96 publications
45
272
1
12
Order By: Relevance
“…Nonetheless, overall our findings seem to confirm the hypothesis of a spectral pattern more proximate to the typical AD profile, mainly in a-md-MCIs. Previous EEG (Babiloni et al 2004;Dauwels et al 2011;Huang et al 2000;Jeong 2004) and MEG studies (Berendse et al 2000;Fernandez et al 2002Fernandez et al , 2003Fernandez et al , 2006b) of AD found an increased power in the low-frequency bands (delta and theta), accompanied by a decreased power in the high-frequency range (alpha, beta, and gamma). Such pattern of spectral changes is a consistent finding that correlates with cognitive performance and functional status (Fernandez et al 2002;Prichep et al 1994;van Deursen et al 2008).…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless, overall our findings seem to confirm the hypothesis of a spectral pattern more proximate to the typical AD profile, mainly in a-md-MCIs. Previous EEG (Babiloni et al 2004;Dauwels et al 2011;Huang et al 2000;Jeong 2004) and MEG studies (Berendse et al 2000;Fernandez et al 2002Fernandez et al , 2003Fernandez et al , 2006b) of AD found an increased power in the low-frequency bands (delta and theta), accompanied by a decreased power in the high-frequency range (alpha, beta, and gamma). Such pattern of spectral changes is a consistent finding that correlates with cognitive performance and functional status (Fernandez et al 2002;Prichep et al 1994;van Deursen et al 2008).…”
Section: Discussionmentioning
confidence: 88%
“…These analyses seem to discriminate AD patients from control subjects through an increased EEG/MEG activity in lower frequency bands associated with this dementia (Babiloni et al 2004;Fernández et al 2006). To be more precise, a decreased mean frequency, an increase in delta and theta power, and a decrease in alpha and beta power are observed in AD patients compared with that of normal elderly subjects (Babiloni et al 2004;Jeong 2004;Fernández et al 2006;Rossini et al 2007). The earliest changes are an increase in theta activity and a decrease in beta activity, which are followed by a decrease in alpha activity, and then an increase in delta activity (Jeong 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In humans, EEG rhythms differ in AD patients compared to normal controls and/or vascular dementia subjects. AD patients were characterized by higher delta (0 -3 Hz), higher theta (4 -7 Hz), lower posterior alpha (8 -12 Hz), slowing in alpha peak frequency, and lower beta (14 -30 Hz) and gamma (around 40 Hz) (Dierks et al, 1993Huang et al, 2000;Wolf et al, 2003;Babiloni et al, 2004;Moretti et al, 2004;Adeli and GhoshDastidar, 2005). The abnormality of EEG rhythms in dementia has been associated with altered rCBF/metabolism and cognitive function (Szelies et al, 1992;Julin et al, 1995;Passero et al, 1995;Sloan et al, 1995;Rodriguez et al, 1999aRodriguez et al, , 1999b.…”
Section: Introductionmentioning
confidence: 99%